Implementasi Manajemen Risiko Studi Kasus : Alur Pengadaan Jasa Rutin Pada Salah Satu Unit di PT XXX Melalui Pendekatan Risk Assessment - Rafida, Halimas Nafi; Rusindiyanto (Jurnal Serambi Engineering, 2025)
Procurement of goods and services is a critical step for an organisation to support its operational activities. This activity plays a vital role in the company's operations and is often faced with potential risks that require accurate and optimal risk mitigation. This study was conducted at a unit of PT XXX to analyse and develop risk mitigation strategies in the procurement process, specifically for routine services. The approach used in this study is risk assessment. The research methods include primary data collection through interviews and observations, as well as related references. The results show that out of 16 activities in the procurement process of routine services, 23 risk analyses were identified. These risks were then categorised according to their risk level: 5 high level risks, 17 medium level risks and 1 low level risk. The risk mitigation strategy planning focuses on the high level risks to control and reduce their impact.